Newborn Screening for Mucopolysaccharidosis I: Moving Forward Learning from Experience - Lorne A. Clarke; Patricia Dickson; N. Matthew Ellinwood; Terri L. Klein (MDPI AG, 2020)
There have been significant advances allowing for the integration of mucopolysaccharidosis I into newborn screening programs. Initial experiences using a single-tier approach for this disorder have highlighted shortcomings that require immediate remediation. The recent evaluation of a second-tier biomarker integrated into the MPS I newborn screening protocol has been demonstrated to greatly improve the precision and predictive value of newborn screening for this disorder. This commentary urges newborn screening programs to learn from these experiences and improve newborn screening for mucopolysaccharidosis I and future mucopolysaccharidoses newborn screening programs by implementation of a second-tier biomarker analyte.